2014
DOI: 10.1038/nprot.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

A nanoparticle formula for delivering siRNA or miRNAs to tumor cells in cell culture and in vivo

Abstract: To improve RNA delivery, we present a protocol to produce an RNA carrier based on a Zn(II)-dipicolylamine (Zn-DPA) analog, which is an artificial receptor for phosphate anion derivatives. We further functionalized this Zn-DPA analog to hyaluronic acid (HA)-based self-assembled nanoparticles (HA-NPS) with a hydrodynamic diameter of 100 nm by conjugating amine-functionalized Zn-DPA molecules onto the HA-NPS through amide formation, resulting in efficient tumor-targeted delivery of RNAs (siRNAs, miRNA or other sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…After the 12-hour dialysis, 131 I-lipiodol loaded micelles were formed and suspended in ultrapure water. The protocol for lipophilic molecules was conducted according to standard procedures [27]. …”
Section: Methodsmentioning
confidence: 99%
“…After the 12-hour dialysis, 131 I-lipiodol loaded micelles were formed and suspended in ultrapure water. The protocol for lipophilic molecules was conducted according to standard procedures [27]. …”
Section: Methodsmentioning
confidence: 99%
“…129 ZnDPA complexes were covalently conjugated to hyaluronic acid-based nanoparticles to enable efficient tumor-targeted delivery of RNAs and small-molecule drugs. 130 ZnDPA-coated nanoparticles were loaded with siRNA specific for a bioluminescence gene within cancer cells were and tested in a mouse colon cancer model. Bioluminescent intensities from tumors treated with RNA-delivering nanoparticles showed a substantial decrease in signal 24 h after injection, demonstrating substantial promise for drug delivery.…”
Section: Therapeutic Applications Using Zndpa Complexesmentioning
confidence: 99%
“…However, it seems that single drugloaded NPs demonstrated some kind of efficacy against tumor growth inhibition but not so efficient. 21 It may be attributed to the tumor heterogeneity, complexity of drug resistance, and barriers of NPs circulating and crossing in vivo. 19,29,30 There are already substantial efforts to incorporate multiple functionalities and moieties within the nanoparticle design.…”
Section: In Vivo Antitumor Efficacymentioning
confidence: 99%
“…Apart from the application in cancer diagnosis, there has been a great interest in developing new nanomaterials for cancer treatment. 20,21 Poly (d,l-lactide-co-glycolide) (PLGA), a biodegradable and biocompatible synthetic polymer approved by the US Food and Drug Administration, is widely used in drug delivery system. [22][23][24] Various studies have reported that multiple drug resistance could be overcome by PLGA NPs codelivering anticancer drug and p-gp inhibitors, indicating that PLGA NPs may be a promising approach to overcome drug resistance.…”
Section: Introductionmentioning
confidence: 99%